Obesity: Epidemiology, Pathophysiology, and Therapeutics - Lin, Xihua; Li, Hong (Frontiers in Endocrinology, 2021)
Obesity is a complex multifactorial disease that excess body fat has accumulated to an extent that it may have a negative effect on health. Obesity continues to accelerate resulting in an unprecedented epidemic that shows no significant signs of slowing down any time soon. Raised body mass index (BMI) is a major risk factor for noncommunicable diseases such as cardiovascular diseases (mainly heart disease and stroke), diabetes, musculoskeletal disorders (especially osteoarthritis), and some cancers, thereby contributing to a decline in both quality of life and life expectancy. The long-term energy imbalance between calories consumed and calories expended is the fundamental cause of obesity. Here, we explore the biological mechanisms of obesity with the aim of providing actionable treatment strategies to achieve a healthy body weight from nature to nurture. This review summarizes the global trends in obesity with a special focus on the pathogenesis of obesity from genetic factors to epigenetic factors, from social environmental factors to microenvironment factors. Against this background, we discuss several possible intervention strategies to minimize BMI.